175k views
1 vote
-2x(x + 1) = -2x + 5

1 Answer

0 votes

we are given


-2x(x+1)=-2x+5

Since, we have to solve for x

so, we will isolate all terms on left side

step-1:

Distribute -2x


-2x* x-2x* 1=-2x+5


-2x^2-2x=-2x+5

step-2:

Add both sides by 2x


-2x^2-2x+2x=-2x+5+2x


-2x^2=5

Step-3:

Divide both sides by -2

and we get


x^2=-(5)/(2)

now, we can take sqrt both sides


√(x^2) =\sqrt{-(5)/(2)}

we get


x=-\sqrt{(5)/(2)}i,x=\sqrt{(5)/(2)}i..............Answer

User Rockfight
by
5.3k points